1989
DOI: 10.1111/j.1365-3016.1989.tb00382.x
|View full text |Cite
|
Sign up to set email alerts
|

The Christchurch Child Development Study: a review of epidemiological findings

Abstract: The Christchurch Child Development Study is a longitudinal study of a birth cohort of 1265 New Zealand children who have been studied over an 11-year period using data from multiple sources including parental interview, medical records, teacher questionnaires and direct testing of children. The article provides a review of the major lines of epidemiological research examined in the Study. These include: breast feeding and child health; parental smoking and child health; the effects of low level lead exposure; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
198
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(201 citation statements)
references
References 75 publications
0
198
0
1
Order By: Relevance
“…These children have been studied at birth, at 4 months, at 1 year, at annual intervals to age 16 years, and again at age 18, using information gathered from a combination of sources including parental interview, teacher report, standardized testing and interviews with the children, and medical records. 19 …”
Section: Methodsmentioning
confidence: 99%
“…These children have been studied at birth, at 4 months, at 1 year, at annual intervals to age 16 years, and again at age 18, using information gathered from a combination of sources including parental interview, teacher report, standardized testing and interviews with the children, and medical records. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Assessments have included : parental interviews, teacher reports, child interviews, standardised psychometric tests, in addition to information obtained from official records and other sources. An overview of the study design has been given previously (Fergusson, Horwood, Shannon, & Lawton, 1989). The data analysed in this report were measured in the following ways.…”
Section: Methodsmentioning
confidence: 99%
“…Information was obtained from a variety of sources including parental interviews, teacher reports, selfreports, psychometric assessments, medical and other recorded data. An overview of the study design and methodology can be found in Fergusson et al (1989) and Fergusson and Horwood (2001).…”
Section: The Christchurch Health and Development Studymentioning
confidence: 99%